Osmotic and pharmacological effects of formamide on capacity current, gating current, and sodium current in crayfish giant axons. - Alicata, D A (1989)
Internal perfusion with solutions made hyperosmolar by 10% formamide selectively reduces the initial fast component of ON gating current (fast Ig) in crayfish axons. This result parallels the effects of formamide perfusion seen in Myxicola giant axons (Schauf, C. L., and M. A. Chuman. 1986. Neural Membranes. Alan R. Liss, Inc., New York. 3-23). However, our findings do not confirm their conclusion that internal formamide has a specific pharmacological effect on fast Ig. Formamide-induced suppression of fast Ig is always associated with changes in linear capacity current, indicating a reduction in the rate of rise of the voltage clamp. Furthermore, this suppression of fast Ig can be reversed when clamp rise time is returned to its control rate by increasing compensation for series resistance (Rs) during formamide perfusion. Increases in Rs during 10% formamide perfusion of up to 5 omega.cm2 were measured by evaluating the increase in Rs compensation required to return the following parameters to their control levels: (a) peak capacity current, (b) peak gating current, (c) the voltage maximum of the /Na-V curve, and (d) "tau h". We conclude that hyperosmolar internal formamide increases Rs, reduces clamp speed, and thus selectively suppresses fast Ig. On the other hand, the reversible block of sodium ionic current by internal formamide, reported by Schauf and Chuman, is not eliminated by correcting for series resistance changes during formamide perfusion.